Management of anti-seizure medications in lactating women with epilepsy - Yan, Rong; Tuo, Jinmei; Tai, Zhenzhen; Zhang, Haiqing; Yang, Juan; Yu, Changyin; Xu, Zucai (Frontiers in Neurology, 2022)
Epilepsy is a common neurological disease. At present, there are about 70 million epilepsy patients in the world, half of them are women, and 30–40% of women with epilepsy are of childbearing potential. Patients with epilepsy who are of childbearing potential face more challenges, such as seizures caused by hormonal fluctuations and the risk of adverse effects on the mother and baby from taking anti-seizure medications (ASMs). Breast milk is one of the best gifts that a mother can give her baby, and breastfeeding can bring more benefits to the baby. Compared with healthy people, people with epilepsy have more concerns about breastfeeding because they are worried that ASMs in their milk will affect the growth and development of the baby, and they are always faced with the dilemma of whether to breastfeed after childbirth. Regarding, whether women with epilepsy can breastfeed while taking ASMs, and whether breastfeeding will adversely affect the baby is still an important topic of concern for patients and doctors. This article reviews the existing research on breastfeeding-related issues in women with epilepsy to guide clinical practice, and improve the breastfeeding compliance of women with epilepsy.